2011
DOI: 10.1038/clpt.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Metabolism After Major Surgery: A Greater Challenge With Increasing Age

Abstract: Patients undergoing major surgery represent a good model for the study of the hepatic metabolism of acetaminophen (APAP) after surgery and for the evaluation of how the detoxification process is influenced by aging. Thirty patients received intravenous APAP (1 g/6 h) for 4 days (D1-D4). Daily 24-h urinary metabolites-cysteine-APAP, mercapturate-APAP, APAP, and glucuronide and sulfate conjugates-as well as blood glutathione levels were compared with repeated-measures analysis of variance (significance, P<0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…These findings are similar to those of Pickering et al (12) who quantified the levels of urinary metabolites after major abdominal (aortic) surgery. In this study, as in ours, a rise in the glutathione dependent metabolites cysteine and mercapturate was observed when compared to early post-operative levels.…”
Section: Page 14 Of 29supporting
confidence: 90%
“…These findings are similar to those of Pickering et al (12) who quantified the levels of urinary metabolites after major abdominal (aortic) surgery. In this study, as in ours, a rise in the glutathione dependent metabolites cysteine and mercapturate was observed when compared to early post-operative levels.…”
Section: Page 14 Of 29supporting
confidence: 90%
“…UTG1A6 is catalyzing the glucuronidation of paracetamol and these haplotypes encode for enzymes with different activity (14,15). Other factors, like age, seem also to impose considerably on the rate of formation of N-sulfate-APAP (16). The presented findings indicate that patients who failed to become afebrile with the first dose of paracetamol, reached defervescence with paracetamol as a rescue medication much slower compared to those administered other agents.…”
Section: Discussionmentioning
confidence: 78%
“…The literature has widely reported that an overdose of APAP as well as therapeutic doses in patients with chronic disease and poor stores of GSH (alcoholism, malnutrition…) may lead to liver dysfunction and/or acute liver failure. A large diminution of whole blood GSH concentration has also been shown after heavy surgery with a few days of 4 g APAP a day. These present findings in young volunteers underline in a healthy population the silent, not readily visible, and poorly acknowledged impact of APAP on GSH stores at therapeutic doses.…”
Section: Discussionmentioning
confidence: 87%
“…It is primarily metabolized in the liver by phase I and II enzymes. Oxidative phase I reactions typically involve several CYP450 isoforms, that catalyze the oxidation of paracetamol to NAPQI (N‐acetyl‐ p ‐benzo‐quinone imine), a toxic metabolite buffered by glutathione (GSH) . Phase II reactions, glucuronidation and sulfation participate to the elimination of the drug.…”
Section: Introductionmentioning
confidence: 99%